Content or status: Frontal and posterior cortical representations of object category and upcoming task goals in working memory. (February 2021) - Olmos-Solis, Katya; van Loon, Anouk M.; Olivers, Christian N.L.
Abstract: To optimize task sequences, the brain must differentiate between current and prospective goals. We previously showed that currently and prospectively relevant object representations in working memory can be dissociated within object-selective cortex. Based on other recent studies indicating that a range of brain areas may be involved in distinguishing between currently relevant and prospectively relevant information in working memory, here we conducted multivoxel pattern analyses of fMRI activity in additional posterior areas (specifically early visual cortex and the intraparietal sulcus) as well as frontal areas (specifically the frontal eye fields and lateral prefrontal cortex). We assessed whether these areas represent the memory content, the current versus prospective status of the memory, or both. On each trial, participants memorized an object drawn from three different categories. The object was the target for either a first task (currently relevant), a second task (prospectively relevant), or for neither task (irrelevant). The results revealed a division of labor across brain regions: While posterior areas preferentially coded for content (i.e., the category), frontal areas carried information about the current versus prospective relevance status of the memory, irrespective of the category. Intraparietal sulcus revealed both strong category- and status-sensitivity, consistent with its hub function of combining stimulus and priority signals. Furthermore, cross-decoding analyses revealed that while current and prospective representations were similar prior to search, they became dissimilar during search, in posterior as well as frontal areas. The findings provide further evidence for a dissociation between content and control networks in working memory.